Transient Gestational and Neonatal Hypothyroidism-induced Specific Changes in Androgen Receptor Expression in Skeletal and Cardiac Muscles of Adult Rat - Annapoorna, K.; Anbalagan, J.; Neelamohan, R.; Vengatesh, G.; Stanley, J.; Amudha, G.; Aruldhas, M. M. (Hormone and Metabolic Research, 2013)
The present study aims to identify the association between androgen status and metabolic activity in skeletal and cardiac muscles of adult rats with transient gestational/neonatal-onset hypothyroidism. Pregnant and lactating rats were made hypothyroid by exposing to 0.05% methimazole in drinking water; gestational exposure was from embryonic day 9–14 (group II) or 21 (group III), lactational exposure was from postnatal day 1–14 (group IV) or 29 (group V). Serum was collected for hormone assay. Androgen receptor status, Glu-4 expression, and enzyme activities were assessed in the skeletal and cardiac muscles. Serum testosterone and estradiol levels decreased in adult rats of groups II and III, whereas testosterone remained normal but estradiol increased in group IV and V, when compared to coeval control. Androgen receptor ligand binding activity increased in both muscle phenotypes with a consistent increase in the expression level of its mRNA and protein expressions except in the forelimb of adult rats with transient hypothyroidism (group II–V). Glut-4 expression remained normal in skeletal and cardiac muscle of experimental rats. Specific activity of hexokinase and lactate dehydrogenase increased in both muscle phenotypes whereas, creatine kinase activity increased in skeletal muscles alone. It is concluded that transient gestational/lactational exposure to methimazole results in hypothyroidism during prepuberal life whereas it increases AR status and glycolytic activity in skeletal and cardiac muscles even at adulthood. Thus, the present study suggests that euthyroid status during prenatal and early postnatal life is essential to have optimal AR status and metabolic activity at adulthood.
Keywords: thyroid hormones; testosterone; estradiol; Glut-4; hexokinase